2012
DOI: 10.1007/s10995-012-1076-x
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Smoking Cessation Quitline Use Among Pregnant and Non-pregnant Women

Abstract: To describe characteristics, referrals, service utilization, and self-reported quit rates among pregnant and non-pregnant women enrolled in a smoking cessation quitline. This information can be used to improve strategies to increase pregnant and non-pregnant smokers’ use of quitlines. We examined tobacco use characteristics, referral sources, and use of services among 1,718 pregnant and 24,321 non-pregnant women aged 18–44 years enrolled in quitline services in 10 states during 2006–2008. We examined self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…Our results also highlight how the four classes of tobacco use differ as a function of demographics and tobacco use-related characteristics. Consistent with previous research, 10 , 31 , 32 age was associated with tobacco product use. Older individuals were more likely to be members of the cigarette user class while the e-cig/hookah user class was more likely to be the youngest among the four classes.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also highlight how the four classes of tobacco use differ as a function of demographics and tobacco use-related characteristics. Consistent with previous research, 10 , 31 , 32 age was associated with tobacco product use. Older individuals were more likely to be members of the cigarette user class while the e-cig/hookah user class was more likely to be the youngest among the four classes.…”
Section: Discussionsupporting
confidence: 91%
“…For example, demand studies 30,31,32,33,34 have obtained prenatal prevalence price elasticities between -0.13 and -0.7, which are consistent with the elasticities used in SimSmoke, and a recent study 34 found higher elasticities for those of low socioeconomic status. Studies have found that other tobacco control policies, including cessation treatment 35,36 , smoke-free air laws 26 , and media campaigns 37 , are effective at reducing prenatal smoking.…”
Section: The Effect Of Policiesmentioning
confidence: 99%
“…These services cover a variety of recommended strategies, such as individual counseling, group behavior therapy, pharmacotherapies (for instance, nicotine replacement therapy), self-help materials, and telephone quitlines [12]. Similar strategies are used in other industrial countries such as the United States [13][14]. However, the guidance for the wide range of cessation treatments has been vague or silent in the timing issue of prenatal smoking cessation or reduction.…”
Section: Introductionmentioning
confidence: 99%